The effect of heterogeneous beliefs on mergers and acquisitions. Issue 8 (4th May 2017) - Deng, Lu; Li, Sifei; Liao, Mingqing
ABSTRACT: This article investigates the effect of heterogeneous beliefs on firms' mergers and acquisitions (M&A) decisions. Using data of China's financial market, which is featured with great heterogeneity of belief, we find that heterogeneous beliefs are positively associated with the occurrence of M&A transactions, and firms with greater heterogeneous beliefs are more likely to pay the transactions with stock. Moreover, we show that government intervention, measured by state ownership, weakens the effect of heterogeneous beliefs on firms' M&A decisions.